Dark and antidark solitons for the defocusing coupled Sasa–Satsuma system by the Darboux transformation. (February 2019) - Zhang, Hai-Qiang; Chen, Fa
Abstract: In this article, we construct the N -fold Darboux transformation for the defocusing coupled Sasa–Satsuma system which describes the simultaneous propagation of two nonlinear waves in optical fibers with higher order effects. With the non-zero constant background as a seed, we derive the dark and antidark soliton solutions from the once-iterated formula. We find that this coupled system can exhibit the dark–dark, dark–antidark and antidark–dark vector solitons.